Development of the Properties of Zinc Polycarboxylate Cement Used as a Basis for Dental Fillings Using Zink Oxide Nanoparticles Prepared by Green Chemistry Method - Hattab, Noor Jabbar; Entisar Eliwi Laibi; Mohammed Mhna Mohammed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Most dental supplies don’t seem to be much of a barrier against germ infiltration. Therefore, the filling must be done with perfect caution and high antimicrobial effectiveness. When dental erosion occurs due to germs that lead to caries, a dental filling is used, creating a small microscopic space between the dental filling and the root end infiltration. This allowed the tooth to be penetrated for the second time, which was the research problem. Adding two compounds to antibacterial fillers (zinc polycarboxylate cement) made them work better: Firstly, was zinc oxide (ZnO) that was made chemically, and secondly, was green ZnO nanoparticles that were made from orange peels and mixed with ZPCC in different amounts. The study was conducted on the formed nanocomposite using FTIR, UV-vis, FESEM, sitting time, and antibacterial measurements. The biological activity was tested using Staphylococcus aureus, Escherichia coli, and Candida albicans.